2020
DOI: 10.1186/s40942-020-00224-1
|View full text |Cite
|
Sign up to set email alerts
|

Outer retina changes on optical coherence tomography in vitamin A deficiency

Abstract: Background: Vitamin A deficiency is rare in the United States and can be missed in patients with malabsorption syndromes without a high dose of suspicion. Ocular complications of hypovitaminosis A include xerosis and nyctalopia, and to a lesser extent reduction in visual acuity and color vision. Outer retinal changes, as seen on spectral domain optic coherence tomography (SD-OCT), in patients with vitamin A deficiency have previously not been documented. Case presentation: We present two cases with symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
2
13
0
2
Order By: Relevance
“…It is understood that the yellowish-white spots observed in the fundus imaging represent shed photoreceptor outer segments above the RPE secondary to loss of phagocytosis function of RPE due to vitamin A deficiency. 3,5 This hypothesis is consistent with the presence of hyperreflective dots between the RPE and the EZ in the OCT that correspond to white-yellowish dots in the fundus of our patient. FAF frequently reveals hypoautofluorescent dots, which may represent localized loss of lipofuscin and blockage of the RPE fluorescence secondary to accumulation of discarded photoreceptor outer segments.…”
Section: Np52supporting
confidence: 90%
See 2 more Smart Citations
“…It is understood that the yellowish-white spots observed in the fundus imaging represent shed photoreceptor outer segments above the RPE secondary to loss of phagocytosis function of RPE due to vitamin A deficiency. 3,5 This hypothesis is consistent with the presence of hyperreflective dots between the RPE and the EZ in the OCT that correspond to white-yellowish dots in the fundus of our patient. FAF frequently reveals hypoautofluorescent dots, which may represent localized loss of lipofuscin and blockage of the RPE fluorescence secondary to accumulation of discarded photoreceptor outer segments.…”
Section: Np52supporting
confidence: 90%
“…These alterations are consistent with an increased susceptibility of the rods to reduced vitamin A levels. 2,4,5 Fundus examination usually reveals white-yellowish spots in posterior pole and midperipheral retina, with corresponding hyperreflective dots between the RPE and the EZ in the OCT. 3,5 Differential diagnosis of fundus imaging and OCT in vitamin A retinopathy must include drusenoid subretinal deposits, which are typically seen in genetic diseases with retinoid cycle dysfunction (such as Sorsby's fundus dystrophy and late-onset retinal degeneration), and in patients with age-related macular degeneration. 10 In our case, we were able to exclude the presence of drusenoid subretinal deposits after the treatment with vitamin A, when we observed the partial resolution of white-yellowish spots in posterior pole.…”
Section: Np52mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Xerophthalmic fundus lesions as presented in this patient are the accumulation of disrupted photoreceptors' outer segments (especially rods) based on histopathological evaluation. [3] According to previous reports of xerophthalmic fundus, the most common finding in OCT is the disruption of the outer retinal layers, especially the ellipsoid zone and SDD-like lesions in the peripheral retina. [3][4][5] Additionally, multicolor imaging was performed and we found that xerophthalmic retinal lesions were much more detectable by fundus multicolor imaging compared to the infrared…”
Section: Discussionmentioning
confidence: 97%
“…Early diagnosis and treatment prevent permanent disruption of photoreceptors and subsequent visual impairment. [3] Financial Support and Sponsorship None.…”
Section: Conflicts Of Interestmentioning
confidence: 99%